2016
DOI: 10.1515/johr-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Ornamental Grasses Under Salinity Stress

Abstract: The aim of this study was to determine the effect of substrate salinity caused by increasing NaCl doses on growth and development of ornamental grasses: Briza media L., Deschampsia cespitosa (L.) P. Beauv., Koeleria glauca (Spreng.) DC., Sesleria caerulea (L.) Ard. and Sorghastrum nutans (L.) Nash. Results provide the basis for the preliminary classification of analyzed grasses in terms of their tolerance to substrate salinity. Grasses, responding negatively to substrate salinity caused by small doses of 5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…This may be due to higher concentration of Na + ions. It is well known that salinity can affect germination of seeds either by creating osmotic potential which prevent water uptake, or by toxic effects of ions on embryo viability (Lisjak et al, 2015;Wu et al, 2015;Henschke, 2016). This is also partly confirmed in our study, whereas the highest percentage of abnormal seedlings (21%) was found at pH 8.5.…”
Section: Discussionsupporting
confidence: 88%
“…This may be due to higher concentration of Na + ions. It is well known that salinity can affect germination of seeds either by creating osmotic potential which prevent water uptake, or by toxic effects of ions on embryo viability (Lisjak et al, 2015;Wu et al, 2015;Henschke, 2016). This is also partly confirmed in our study, whereas the highest percentage of abnormal seedlings (21%) was found at pH 8.5.…”
Section: Discussionsupporting
confidence: 88%
“…However, these authors described the resistance features at salinity levels between 15 and 30 g NaCl•dm -3 . Henschke [2017] defined S. caerulea and S. nutans as a halophyte, and in those grass, RWC did not decrease under the influence of salinity. Glenn [1987] also found that Spartina sp.…”
Section: Resultsmentioning
confidence: 87%
“…В таких условиях, к весне, концентрация солей в почве на близлежащих территориях резко повышается, что является причиной угнетения растительности, в первую очередь травянистой, имеющей поверхностную корневую систему. Высокая концентрация солей приводит к нарушению синтеза хлорофилла и, как следствие, к уменьшению размеров листьев, постепенному их увяданию в акропетальном направлении и гибели растений [27,34,42]. Поэтому злаки, приспособленные к произрастанию в условиях повышенной засолённости и отличающиеся высокой засухоустойчивостью (Calamagrostis epigejos (L.) Roth, Leymus arenarius (L.) Hochst, Leymus racemosus (Lam.)…”
Section: таблица 1 происхождение высокорослых декоративных многолетни...unclassified